Women coaches at top level: Looking back through the maze - Borrueco, M.; Torregrossa, M.; Pallarès, S.; Vitali, F.; Ramis, Y. (International Journal of Sports Science & Coaching, 2023)
Framed in the Ecological-Intersectional Model and the Stages of Career Progression Model, the objective of this study was to explore how women coaching in high-performance settings advanced through the `bottle-neck` path. In total 13 women coaches from Southern Europe between the age of 28 and 46 years working in high-performance contexts were interviewed. In order to assess both the subjective perceptions of participants and the structural factors that prevent women from accessing top-level positions, we adopted a critical realist perspective to perform a thematic analysis. Results show that while women coaches may follow a linear coaching career path in their early career stages, once they try to progress to high-performance settings their careers are shaped by the metaphor of a maze. Women need to navigate through a maze while having to overcome jeopardizing factors to find a succeeding career path in sports coaching. Moreover, previous experience as elite athletes, close entourage, role models, organizational support, precarious working conditions and motherhood influenced women's development of a coaching career, with differing relevance depending on the career stage. Women coaches who reach top-level positions associate their success with casual or external factors, instead of causal explanations related to their own achievements. We add evidence on the specificities of women's coaching careers that should be addressed not only to improve their recruitment and professional progression, but also to work on reducing the probabilities of women exiting the role.